Կիլիկյան Հայաստանում հանգրվանած եվրոպացիների ամուսնություններն ու արտամուսնական պայմանագրերը - Գևորգյան, Զոհրաբ («Նաիրի» հրատ.)
It is well known that many representatives of the ruling elite in Cilician Armenia, including princes and kings, had marital relations with the famous European dynasties of the time. But such relationships between the nobility and the ordinary citizens of Cilician Armenia on the one hand, and the Europeans who lived at the time in the Cilician cities on the other, have not been of much interest to researchers. As a matter of fact, particularly hundreds of Genoese lived for a long time in Laiazzo (Ayas). Naturally, these men sought marital or extra-marital relationships with the residents of Cilician Armenia. The study of this topic may allow to identify a wide range of questions about life in the Armenian Kingdom of Cilicia. Общеизвестным фактом являются брачные отношения многих представителей элиты Киликийской Армении, в том числе князей и королей, с известными европейскими династиями того времени. Но подобные отношения между дворянством и обычными жителями Киликийской Армении с одной стороны и европейцами, проживавшими в то время в киликийских городах, с другой, не привлекали внимания исследователей. Можно утверждать, что, сотни генуэзцев жили в Аясе в течение месяцев и многих лет. Естественно, что эти люди имели брачные и внебрачные связи с жителями Киликийской Армении. Изучение этой темы таит в себе возможности для выявления широкого круга вопросов истории повседневной жизни в Киликийском армянском царстве.
Keywords: Պատմություն; Ընտանեկան հարաբերություններ; Կիլիկյան Հայաստան